Analysis of Additions and Changes in the Curriculum of the Subject "Bases of Health" 6-9 Grades in Connection with the War - Zaplatynskyi, Vasyl (Educological discourse, 2023)
The main ideas of the publication of the analysis of additions and changes in the program of the "Basics of Health" subject for grades 6-9 were the identification of key changes to the programs and the determination of the prospects for their changes in the next 2023/2024 academic year. Changes and additions to the program of the subject "Basics of health" were made in 2022 in connection with Russian aggression. Most of the changes and additions are aimed at the formation of competences that allow to reduce the risks of military operations, to preserve life and health in the occupied, liberated and controlled territories of Ukraine. The peculiarity of the changes in the program is that they concern the same topics in each of the classes. This is justified and necessary from the point of view that these competencies must be mastered by students of all age groups as quickly as possible. This circumstance will require a significant revision of the added changes in 2023 in order to avoid unjustified repetitions and for the spiral deployment of knowledge and the complexity of the material in accordance with the age. The presented research results, in addition to the theoretical ones, pursue several practical problems. First of all, the content that must be added to the integrated course "Health, safety and well-being" for the 5th grade, and in the 2023/2024 academic year to the topics of the 6th grade, is highlighted. Analysis and comparison of additions to the program in each grade will enable teachers of the "Basics of Health" subject to plan the topic and its features in grades 6-9. The information presented in the presented study for teachers of the subject "Defense of Ukraine" is important, due to the fact that the topic of protection from military dangers is considered in this subject. The presented analysis may be of interest to the authors during the development of model programs of the integrated course "Health, safety and well-being" for grades 7, 8, 9.